2018
DOI: 10.3389/fphar.2018.00586
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Enoxaparin in Lichen Planus: Exploring Reasons for Inconsistent Reports

Abstract: Lichen planus (LP) is an uncommon mucocutaneous inflammatory condition, that is immunologically mediated, typically pruritic and often recurs. The currently advocated therapies are either not highly effective or associated with severe side effects. Enoxaparin, a widely used anticoagulant, is composed of both anticoagulant and non-anticoagulant fragments. Enoxaparin is reported to have anti-inflammatory properties and it was found to be effective in LP. However, the results from clinical studies have varied sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Apparently, clinical studies in the current literature have come out with inconsistent results: while some studies showed encouraging results, others had disappointing outcomes. Patel et al have recently investigated the potential reasons behind these discrepancies and they have suggested the following explanations: (i) the variable study designs, (ii) the use of subtherapeutic dose of enoxaparin and (iii) batch‐to‐batch inconsistency in the enoxaparin formulation. Better designed RCT are demanded to clarify the efficacy, safety and tolerability of enoxaparin in LP in future.…”
Section: Enoxaparin Sodiummentioning
confidence: 99%
“…Apparently, clinical studies in the current literature have come out with inconsistent results: while some studies showed encouraging results, others had disappointing outcomes. Patel et al have recently investigated the potential reasons behind these discrepancies and they have suggested the following explanations: (i) the variable study designs, (ii) the use of subtherapeutic dose of enoxaparin and (iii) batch‐to‐batch inconsistency in the enoxaparin formulation. Better designed RCT are demanded to clarify the efficacy, safety and tolerability of enoxaparin in LP in future.…”
Section: Enoxaparin Sodiummentioning
confidence: 99%
“…In the literature, there are mostly open-ended and nonrandomized studies involving a small number of patients and investigating the efficacy of subcutaneous enoxaparin in lichen planus (18)(19)(20)(21)(22). In the single randomized study, Iraji et al (23) compared the efficacy of low-dose enoxaparin with oral prednisolone and concluded that, although its therapeutic efficacy is lower than that of oral prednisolone, low-dose enoxaparin has therapeutic efficacy in lichen planus and that it may be a safer treatment alternative with fewer side effects.…”
Section: Discussionmentioning
confidence: 99%